13(-7-9x)+55x+63=-93

Simple and best practice solution for 13(-7-9x)+55x+63=-93 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(-7-9x)+55x+63=-93 equation:



13(-7-9x)+55x+63=-93
We move all terms to the left:
13(-7-9x)+55x+63-(-93)=0
We add all the numbers together, and all the variables
13(-9x-7)+55x+63-(-93)=0
We add all the numbers together, and all the variables
55x+13(-9x-7)+156=0
We multiply parentheses
55x-117x-91+156=0
We add all the numbers together, and all the variables
-62x+65=0
We move all terms containing x to the left, all other terms to the right
-62x=-65
x=-65/-62
x=1+3/62

See similar equations:

| p/8=7/3 | | 5.3x+1.3=7+7.3x | | -90(x+6)=-207 | | -31=-2r+7 | | s+40/9=10 | | 11z+z-2z+5z-14z=25 | | m/0.4=6 | | 91n+6+5n-31=203 | | 112+(5x-8)+(6x-12)=180 | | z/3+14=17 | | x/4-15=25 | | 13/4x22/3=x | | 12d-10d+2d+7d-10d=30 | | -8(7-9x)+54=-146 | | 7(-6x+1)=259 | | 10x4x= | | 4*x/60=1 | | 12((y+1)/(4))+5y=0 | | Y=22x-77 | | 59+(x+40)+(2x)=180 | | -5d+7d=72 | | (10z+17)+(2z+25)=180 | | 29a-13a-12a-3a=14 | | 29a-13a-12a-3a=13 | | x-37=4(2x+3)-7 | | (15x)=(540+9x) | | -7(3x-9)+15x=-33 | | 56.4.5x=110 | | 2(x-5)-29=24-5x | | 6=15-3*x | | 33n+8n+2n-24n=19 | | 33d-20d-6d+2d-6d=27 |

Equations solver categories